2013
DOI: 10.4021/wjon663e
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Antitrypsin Blood Levels as Indicator for the Efficacy of Cancer Treatment

Abstract: BackgroundAlpha-1 antitrypsin (α1-AT) is a member of the serine protease inhibitors (serpins) family. Liver cells are the major source of synthesis and secretion of (α1-AT) into the blood. Moreover, it has been demonstrated that α1-AT is expressed and secreted by many types of malignant cells. Studies have indicated that serum levels of (α1-AT) increase in a good number of malignant diseases. In addition, a significant correlation between serum levels and cancer stage has also been reported. In this work we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…It has been also suggested that the main source of the increase in blood levels of this protein in cancer patients is the growth of cancer cells [ 47 ]. In a recent survey, also of lung cancer and prostate cancer, a decrease in the serum levels of SERPINA1 was observed several weeks after treatment, suggesting that it may be an important indicator of the effectiveness of cancer treatment [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been also suggested that the main source of the increase in blood levels of this protein in cancer patients is the growth of cancer cells [ 47 ]. In a recent survey, also of lung cancer and prostate cancer, a decrease in the serum levels of SERPINA1 was observed several weeks after treatment, suggesting that it may be an important indicator of the effectiveness of cancer treatment [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Decreased levels of SERPINA1 in hyperthyroid state may indicate a decrease in the inhibitory activity of the enzyme on the proteases and an increased inflammatory state [ 25 ]. Alternatively, elevated levels of SERPINA1 have been observed in inflammatory diseases and different types of malignancies, including thyroid cancer [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the positive association between upregulation of A1AT expression levels with cancer staging has been demonstrated in different types of cancer (21,22). El-Akawi et al (23) demonstrated the potential use of A1AT blood levels as an indicator of lung and prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%